TREATMENT OF RADIATION-INDUCED PELVIC DAMAGE AFTER RADIATION THERAPY FOR PROSTATE CANCER - I. V. Sycheva (Сибирский онкологический журнал, 2018)
Background. Radiation-induced damage to the pelvic organs (post-radiation proctitis, cystitis, urethritis) is a frequent complication after radiotherapy for prostate cancer. The reported frequency of late  radiation damage to the pelvic organs is up to 30 %.Material and methods. The paper presents treatment outcomes of 149 with radiation-induced pelvic injuries caused by brachitherapy  (15 patients) and combination treatment including brachitherapy and external beam radiation therapy (28 patients) for stage T1–3N0M0  prostate cancer. Radiationinduced rectitis (proctitis) was revealed in  149 patients and complications of the urinary tract after radiation treatment were noted in 107 (72 %) patients. Potency  failure was observed in 98 % of cases. All patients received  conservative treatment and 8 (5 %) of these patients underwent  surgery after inefficient conservative treatment. Results. Favorable effect of conservative therapy of radiation-induced rectitis was obtained in 141 (95 %) patients. Eight (5 %)  patients underwent colostomy due to the formation of vesicle-rectal  fistula. Chemical cauterization of the mucosa of the bladder and  rectum in patients with erosive hemorrhagic and hemorrhagic rectitis and cystitis was effective and safe. The frequency of post-radiation  complications was found to be less after brachitherapy than after  combination treatment using brachitherapy and external beam  radiation.